Helicobacter pylori infection increase the risk of subclinical hyperthyroidism in middle-aged and elderly women independent of dietary factors: Results from the Tianjin chronic low-grade systemic inflammation and health cohort study in China - Zhang, Juanjuan; Hai, Xinghua; Wang, Siyu; Zhu, Fan; Gu, Yeqing; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Zhang, Shunming; Zhang, Tingjing; Wang, Xing; et al. (Frontiers in Nutrition, 2023)
Background Prospective studies on the association between Helicobacter pylori (H. pylori) infection and subclinical hyperthyroidism are limited. We, therefore, designed a large-scale cohort study to explore the association between H. pylori infection and the risk of subclinical hyperthyroidism in women. Methods This prospective cohort study investigated 2,713 participants. H. pylori infection was diagnosed with the carbon 13 breath test. Subclinical hyperthyroidism was defined as serum thyroid-stimulating hormone levels are low or undetectable but free thyroxine and tri-iodothyronine concentrations are normal. Propensity score matching (PSM) analyses and Cox proportional hazards regression models were used to estimate the association between H. pylori infection and subclinical hyperthyroidism. Results A total of 1,025 PS-matched pairs of H. pylori infection women were generated after PSM. During 6 years of follow-up, the incidence rate of subclinical hyperthyroidism was 7.35/1,000 person-years. After adjusting potential confounding factors (including iodine intake in food and three main dietary patterns score), the multivariable hazard ratio (HR; 95% confidence intervals) of subclinical hyperthyroidism by H. pylori infection was 2.49 (1.36, 4.56). Stratified analyses suggested a potential effect modification by age, the multivariable HR (95% confidence intervals) was 2.85 (1.45, 5.61) in participants aged ≥ 40 years and 0.70 (0.08, 6.00) in participants aged < 40 years (P for interaction = 0.048). Conclusion Our prospective study first indicates that H. pylori infection is significantly associated with the risk of subclinical hyperthyroidism independent of dietary factors among Chinese women, especially in middle-aged and older individuals. Clinical Trial Registration:https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000031137, identifier UMIN000027174.